A prospective observational pilot study of adverse drug reactions contributing to hospitalisation in a cohort of middle-aged adults aged 45- 64 years. - Grimes, Tamasine; Widdowson, Matt (My University, 2020)
Purpose: Determine the prevalence, severity and preventability of adverse drug reactions (ADRs), ADRs causing or contributing to hospitalisation (cADRs) and preventable ADRs (pADRs) in middle-aged patients aged 45-64 years presenting acutely to hospital. Methods: Prospective observational pilot study. The sampling frame was middle-aged patients in the Acute Medical Unit of an Irish university teaching hospital. 100 patients using ≥3 medicines were screened for ADRs present at hospitalisation. Potential ADRs were assessed for causality, preventability, severity and relationship to hospitalisation using validated tools and clinician assessment. The associations between ADRs and potentially inappropriate prescribing (PIP) and polypharmacy (≥5 medicines) were investigated using the Pearson’s chi-squared test. Multi-variate logistic regression analyses examined association between ADRs and sex, age, polypharmacy, co-morbidity and PIP. Results: Twenty-one of 100 patients experienced 23 ADRs. Prevalence of cADR and pADR was 14% and 11% of patients respectively. Over half of ADRs identified (n=14) were sufficiently severe to prompt presentation to hospital for urgent medical review. PIP was associated with occurrence of any ADR (adjusted odds ratio 3.49, 95% CI 1.22-9.93), but not with cADR. Excessive polypharmacy (≥10 medicines) (χ2=5.73, p=0.02), but not polypharmacy, was associated with any ADR occurrence. Conclusions: One in five patients had an ADR and experienced short-term morbidity as a result. For 11 patients, the experienced ADR was preventable. These findings illustrate that middle-aged patients are vulnerable to medicine-related harm. Additional research in larger studies is needed to more comprehensively describe ADR prevalence in middle-age as well as the risk factors for same.
PUBLISHED
Keywords: Middle age; Adverse drug reaction; Hospitalisation; Polypharmacy; Potentially inappropriate prescribing; Ageing; Inclusive Society; ADVERSE DRUG REACTIONS; Medication safety; Patient safety